An Uncommon Manifestation of a Great Imitator: Gummatous Syphilis of the Liver in an HIV-Positive Patient - Nadia Solomon; Tom Heller; Tommaso Manciulli; Paola Del Giacomo; Katleen de Gaetano Donati; Enrico Brunetti; Francesco Taccari (Case Reports in Infectious Diseases)
Syphilis is a sexually transmitted infection caused by Treponema pallidum. It progresses in phases and undiagnosed disease can cause considerable morbidity. Tertiary syphilis causes the formation of gummas. Liver involvement is rarely described and usually limited to transaminase elevation during primary syphilis. We present a case of tertiary syphilis in an HIV patient. Microbiological, clinical, and radiological information were retrieved from the patient’s record. Gummatous syphilis is rarely described in the literature, and practicing physicians should be aware of its existence and include this manifestation in the differential diagnosis of patients with a positive serology and focal liver lesions.